2016
DOI: 10.1109/tcst.2015.2502898
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Control of Stick-Slip Oscillations in Drilling Systems

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 40 publications
(147 reference statements)
1
41
0
Order By: Relevance
“…It showed that the axial stick-slip phenomenon is dependent on the rotational bit speed and that the generation of torsional stick-slip phenomenon is driven by the axial motions, which means that mitigation of axial vibrations may also suppress torsional vibration. Besselink et al 67 furthered the work of mitigation of stick-slip vibration by using feedback control strategies.…”
Section: Stick-slip and Bit Bounce Coupling Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed that the axial stick-slip phenomenon is dependent on the rotational bit speed and that the generation of torsional stick-slip phenomenon is driven by the axial motions, which means that mitigation of axial vibrations may also suppress torsional vibration. Besselink et al 67 furthered the work of mitigation of stick-slip vibration by using feedback control strategies.…”
Section: Stick-slip and Bit Bounce Coupling Modelsmentioning
confidence: 99%
“…Besselink et al. 67 furthered the work of mitigation of stick–slip vibration by using feedback control strategies.…”
Section: Stick–slip Vibration Coupling Modelsmentioning
confidence: 99%
“…Severe drill string vibration will lead to increased dynamic stress of the drill pipe, premature failure of the drill string, affecting the service life of the drill bit and causing interference to the drilling measurement system, resulting in an increase in economic costs, affecting drilling speed and drilling efficiency and in severe cases may lead to downhole accidents [5][6][7][8][9]. Therefore, the research on the dynamics of the drill string related to the vibration of the drill string has become a hot topic in current research and the related research has important economic benefits and practical guiding significance [10][11][12][13]. During the drilling process, when the hard formation is encountered, it is necessary to increase the weight of the drill or replace the drill bit to achieve the rock fracture [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in Liu et al (2014), a coupled axialtorsional model with state-dependent delay is considered. In Besselink et al (2016), a feedback control strategy to mitigate torsional stick-slip oscillations using a coupled axial-torsional model for the drill-string is proposed.…”
Section: Introductionmentioning
confidence: 99%